The DBS Handbook Of Remote Sensing - Shoaib, Mohammad (New Delhi: Dbs Imprints, 2019)
Remote Sensing is the science of obtaining information about objects or areas, from a distance, typically from aircrafts or satellites. Remote sensors collect data by detecting the energy that is reflected from Earth. These sensors can be fitted on a satellite or mounted on an aircraft. Remote sensors can either be passive or active. Passive sensors respond to external stimuli. They record natural energy that is reflected or emitted, from the Earth$1 (Bs surface. The most common source of radiation detected by passive sensors, is the reflected sunlight. In contrast, active sensors use internal stimuli to collect data, about Earth. Remote Sensing is the process of detecting and monitoring the physical characteristics of an area by measuring its reflected and emitted radiation, at a distance, from the targeted area. Remote Sensing is a significant topic, under Physical Sciences. In modern education system, it has evolved into a valuable subdiscipline of these Sciences. This book serves the purpose, for a textbook, as well as, a reference manual, for students, teachers, researchers, scientists and of course, the general readers.s
Includes Glossary, Bibliography and index
Keywords: Remote sensing; Geographic information systems; Satellite imaging; Earth